Influences of different factors of Hevea brasiliensis callus induction - Ming Cong; Huiqin Huang; Jiasen Lv; Shixiang Bao (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.111-114.)
In order to get calli, two kinds of explants are utilized to induce calli, anthers and integument of immature seeds. For anthers callus induction, 2,4-D 4.0 mg/L and 6-BA 0.5 mg/L is the best combination. And 2,4-D 4.0 mg/L and KT 0.2 mg/L is the best for integument callus. THe whole culture effect of different cultivars is Haiken No.2> 88-13> Haiken No.1>73397. In addition,degree of medium consolidation can also be affect the induction effect, consolidation>semi-consolidation. Maltose is used as carbon souce in primary medium while sucrose in subculture medium in order to keep calli from browning and to get large quantities of calli. AgNO3 and air exchanging properly will benefit callus induction. For 73397 cultivars, it is easier for integuments to be induced into callus than anthers.
Keywords: Anther; Callus induction; Hevea brasiliensis; Integument; Plant hormones